Assessment of the nutrition intake of lactating women in Jakarta: Before pandemic strikes - Diana Sunardi; Dian Araminta Ramadhania; Fransisca Olivia; Reisa Melisa Wijaya; Saptawati Bardosono (World Nutrition Journal, 2022)
Nutrition is important for immune system. Lactating women are more susceptible to nutrient deficiencies therefore diseases. More attention to the intake status of lactating women is needed in order to optimize intervention when required. The aim of this study was to assess the adequacy of nutrient intake of lactating women in Jakarta